The mediating role of higher-order thinking skill in the relationship between mathematics strength and achievement in electrical and electronic engineering education - Oduro-Okyireh, Theodore; Mulyanti, Budi; Rohendi, Dedi; Oduro-Okyireh, George; Mensah, Alice Constance; Acheampong, Kennedy (Nurture, 2024)
Purpose: The paper aims to examine the casual role of higher-order thinking skills as a mediator in the relationship between students’ strength in mathematics and achievement in electrical and electronic engineering education. Design/Methodology/Approach: The study adopted a quantitative research design where random cluster sampling was used to select a total of 488 final-year students from four technical universities in Ghana. Mathematics achievement tests were used to gather data on students’ higher-order thinking skills and competence in five areas of mathematics. Also, their examination results were collected from their respective universities. Mediation analysis was done using AMOS 26. Finding: The study revealed that the positive effect of students’ strengths in the five selected mathematics topics on their performance in electrical and electronic engineering education is mediated by their higher-order thinking skills. Conclusion: The research concludes that there is a partial mediation in the relationship between students’ strength in mathematics and achievement in electrical and electronic engineering education by higher-order thinking skills. Research Limitations: It is recommended that further researchers carry out similar research with more mathematics indicators to explain more variations in achievement in electrical and electronic engineering education. Practical Implication: Engineering mathematics curriculum developers should stress the need for mathematics, especially algebra, for the development of higher-order thinking skills to facilitate problem-solving in electrical and electronic engineering education and practice. Contribution to Literature: This study highlights the relationship between the understanding of the concepts of specific mathematics topics, higher-order thinking skills, and achievement in electrical and electronic engineering education.